ANALISIS PENGGUNAAN APLIKASI DARING DI SD XAVERIUS 3 PALEMBANG SELAMA PANDEMI COVID-19 - Boni Fasius Aviandra Bayu (Universitas Katolik Musi Charitas, 2021)
During the Covid-19 pandemic, SD Xaverius 3 Palembang experienced several obstacles, so the school decided to do online learning using an online application. The purpose of this study was to determine the use of online applications during the covid19 pandemic, the supporting factors during the use of online applications and the strategies used during the use of online applications. This type of research is qualitative using descriptive method. Data collection techniques were carried out using a questionnaire/questionnaire method and triangulated using the interview method. The results of this study, online applications used by teachers are zoom, google meet, google forms, google classroom, google email, whatsapp group and telegram. The teachers also said that the supporting factors obtained so far were wifi, internet quota, ipad, flash disk and attending trainings on the use of online applications organized by schools, UKMC lecturers and the Xaverius Palembang Foundation. The teachers also use additional applications such as kine master, bandicam, xrecorder and youtube. Communication tools such as cellphones and laptops are also sufficient and 80% of teachers replace cellphones. While the strategy used is to make online lesson plans, PPT slide shows and videos. However, the teachers experienced problems while using the online application. The problem is the slow wifi network because all the teachers use it and the weather factor. Time constraints are also an obstacle, because they work with super extras and students who are getting bored with online learning.